2014
DOI: 10.1039/c4cp03241a
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel deposited Cu2O and CuO thin films for photocatalytic water splitting

Abstract: Cu2O and CuO are attractive photocatalytic materials for water splitting due to their earth abundance and low cost. In this paper, we report the deposition of Cu2O and CuO thin films by a sol-gel spin-coating process. Sol-gel deposition has distinctive advantages such as low-cost solution processing and uniform film formation over large areas with a precise stoichiometry and thickness control. Pure-phase Cu2O and CuO films were obtained by thermal annealing at 500 °C in nitrogen and ambient air, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
155
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 40 publications
10
155
1
1
Order By: Relevance
“…As the CuO film thickness increases, more light can be absorbed until a certain thickness, whereby the CuO films will reduce the light photon penetration. This will increase the electron-hole pair recombination rate and results in a lower water-to-hydrogen conversion efficiency [4]. From Figure 5, it was found that the photocurrent density increased with increasing CuO nanocrystals size.…”
Section: Preparation Of Cuo Thin Films Electrodeposition Ofmentioning
confidence: 87%
See 2 more Smart Citations
“…As the CuO film thickness increases, more light can be absorbed until a certain thickness, whereby the CuO films will reduce the light photon penetration. This will increase the electron-hole pair recombination rate and results in a lower water-to-hydrogen conversion efficiency [4]. From Figure 5, it was found that the photocurrent density increased with increasing CuO nanocrystals size.…”
Section: Preparation Of Cuo Thin Films Electrodeposition Ofmentioning
confidence: 87%
“…Lim et al [4] studied the deposition of Cu 2 O and CuO thin films by a sol-gel spin-coating process, and enhanced the PEC performance by depositing a thin layer of NiO x co-catalyst. Wang et al [6] investigated the effect of deposition voltage on the morphology of CuO thin films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slope increased with the particles fluence, indicating that the lowest resistance corresponded to the batch implanted with 4 Â 10 16 particles/cm 2 . The observed decrease in the resistance can be attributed to two phenomenon (a) increase in the dopant concentration doe to increase in the fluence and (b) transformation of Cu 2 O phase to a CuO phase which exhibits higher electrical conductivity than Cu 2 O [37]. From these results, it may be surmised that the optical and the XRD studies were significant to understand the effect of low energy ion implantation as a post depositional method on the copper oxide thin film deposited by PLD technique.…”
Section: Optical Propertiesmentioning
confidence: 82%
“…Constructing junctions is a common and effective way to promote charge separation and prolong charge carriers lifetimes [11]. Recently several new related works pointed out that the property of CuO can be improved by modifying Ag [12] nanoparticless or Cu 2 O [13]. These strategies are regarded to improve the light harvesting ability to enhance the photocatalytic activities.…”
Section: Introductionmentioning
confidence: 98%